Komunikasi Dakwah dalam Kewajiban Berjilbab di Indonesia - Rambe, Elismayanti; Hasibuan, Susanti; Handayani, Suci (FDIK IAIN Padangsidimpuan, 2024)
Regulations established by several government authorities to regulate the obligation to wear the hijab and wear Islamic clothing are considered a form of gender discrimination against women, however, if viewed from the perspective of da'wah communication, the hijab is a symbol and medium for conveying da'wah. The aim of the research is to examine the background to the birth of the policy which requires women to wear the hijab, and whether this has a significant correlation with the real protection of women in society and whether there are elements of the application of Islamic law which contains da'wah in regulations in several regions in Indonesia. This research uses the library research method by using statutory regulations, whether formed based on Mayor, Regent or Regional Regulations, as the research object. Based on data obtained from regulations and primary literature, the research results will be reduced and arranged according to the research sequence, then processed into research data.